Pengaruh Pemberian Terapi Audio Murottal Qur’an Surat Ar - Rahman terhadap Tingkat Kecemasan pada Pasien Pre-Operasi Katarak Senilis - Syafei, Abdul; Suryadi, Yogik (Politeknik Kesehatan Tanjungkarang, 2018)
The cataract’s prevalence was still high in Indonesia, according to medical record data of Eye South Sumatera Province Hospital, the year 2016, found that Senile cataracts were ranked first of the top 10 outpatient diseases, amounted 8.275 people. According to the Health Ministry of Indonesia, the year 2014, 8.1% patient have fear of surgery or anxiety. This study was to determine the effect of murrotal audio therapy of Qur'an Surah Ar-Rahman to the level of anxiety in pre-surgery senile cataract patients at Eye Hospital of South Sumatra Province. The design of this research was pre-experiment using quantitative approach. Primary data were obtained through interviews and observations using questionnaires, before intervention and after the intervention. The number of samples was 56 respondents and taken by accidental sampling technique. Data were analyzed by univariate and bivariate analysis with Nonparametric statistical test, Marginal Homogeneity Test. The result showed that patients with anxiously heavy was 28 people (50.0%) before the murottal treatment of Qur'an Surah Ar-Rahman, and patients with anxious very heavy were 28 people (50.0%). After intervention or treatment using murottal audio therapy Qur'an Surah Ar-Rahman, 16 people (28.6%) were moderate anxiety, 35 people (62.5%) were anxiously heavy, and 5 people (8.9%) were anxious very heavy. It can be concluded that there was the influence of anxiety differences of respondents before and after given audio therapy Qur'an Surah Ar-Rahman.